2020
DOI: 10.1177/2325958220934606
|View full text |Cite
|
Sign up to set email alerts
|

The Convergence of Disclosure Concerns and Poverty Contributes to Loss to HIV Care in India: A Qualitative Study

Abstract: In India, there is little evidence on reasons for high rates of loss to HIV care. We conducted a clinic-based qualitative study at the YR Gaitonde Centre for AIDS Research and Education to explore factors that influence loss to care. In all, 17 men and 14 women were interviewed; median age was 42 (interquartile range [IQR], 36-48) and median CD4 count was 448 (IQR, 163-609). A majority reported avoiding treatment freely available at nearby government facilities because of disclosure concerns and perceptions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Likewise, a previously reported study in India ascertained that patients tended to postpone engaging in medical care until their CD4 counts became lower owing to economic limitations. 42 Apart from poverty, fear of adverse effects of ART would also potentially contribute to the non-initiation of ART among PLHIV. This study revealed that the anticipation of drug side effects could discouraged the participants from initiating antiretroviral therapy early.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a previously reported study in India ascertained that patients tended to postpone engaging in medical care until their CD4 counts became lower owing to economic limitations. 42 Apart from poverty, fear of adverse effects of ART would also potentially contribute to the non-initiation of ART among PLHIV. This study revealed that the anticipation of drug side effects could discouraged the participants from initiating antiretroviral therapy early.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, spousal HIV status was the strongest predictor of HIV positivity in the women studied, followed by poverty which is well established by health disparities research. 23 Observed age trends indicate that HIV transmission may occur soon after marriage, reinforcing the need for HIV prevention interventions immediately after marriage. In particular, increased access to broad-based couples-based HIV counseling and testing (HCT) pre- and post-marriage is an important first step.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, participants preferred private facilities to public facilities because of unconsented disclosure which was also highlighted earlier that participants chose to receive care from private facilities than public facilities because of concerns over sero-status disclosure and added that care provided at public hospitals was inferior to care at private facilities. 31 People living with HIV are willing to spend money to receive treatment in a more confidential setting instead of utilizing the free care at the public health facilities to avert unintended disclosure. 31 This implies that Reinforcing confidentiality policy and human rights sensitization in these hospitals will help to minimize unintended disclosure thereby reducing HIV-related stigma.…”
Section: Discussionmentioning
confidence: 99%
“… 31 People living with HIV are willing to spend money to receive treatment in a more confidential setting instead of utilizing the free care at the public health facilities to avert unintended disclosure. 31 This implies that Reinforcing confidentiality policy and human rights sensitization in these hospitals will help to minimize unintended disclosure thereby reducing HIV-related stigma.…”
Section: Discussionmentioning
confidence: 99%